pH-dependent contribution of chlorine monoxide radicals and byproducts formation during UV/chlorine treatment on clothianidin - Lee, Youn Jun; Lee, Chang Gu; Park, Seong Jik; Moon, Joon Kwan; Alvarez, Pedro J.J. (Chemical Engineering Journal, 2022)
Combining UV and free chlorine (UV/chlorine) is an efficient advanced oxidation process for the abatement of recalcitrant organic compounds in drinking water and wastewater. This study investigated the degradation of a neonicotinoid insecticide, clothianidin (CTD), by UV/chlorine treatment. The free chlorine concentration was optimized at 160 μM, and 90.1 ± 0.4% of 40 μM CTD was degraded after 300 s of treatment. Radical quenching tests using tert-butyl alcohol, Cl−, HCO3−, and N3− indicated that chlorine monoxide (ClO•) was the main radical species for CTD degradation. The second-order rate constants of CTD reacting with ClO• (kClO•,CTD = 7.3 ± 0.1 × 109 M−1s−1) was 4.3 times higher than that for •OH (k•OH,CTD = 1.7 ± 0.2 × 109 M−1s−1). The presence of humic acid inhibited CTD degradation by filtering UV and scavenging ClO•. The pH was optimized at 7, and the overall reaction rate constant (k′) was 2.35 ± 0.02 × 10−2 s−1 (half-life = 0.49 min). Degradation products identified during the UV/chlorine treatment were 1-methyl-3-nitroguanidine ([M + H]+ = 118.9), nitroguanidine ([M + H]+ = 105.1), methylguanidine ([M + H]+ = 74.3), and clothianidin urea ([M + H]+ = 206). The detailed time-dependent concentrations of the generated products under different pH conditions were also provided. The results suggest that the UV/chlorine treatment can be an efficient strategy for CTD degradation.
Keywords: Chlorine monoxide; Chlorine treatments; Clothianidin; Degradation kinetics; Free chlorine; Nitroguanidine; PH-dependent; Reactive chlorine species; Solution pH; UV and free chlorine; Clothianidin; Degradation kinetics; Reactive chlorine species; Solution pH; UV/chlorine